The effects of alcohol consumption on the hypertrophy process (Research, Society and Development, 2022)
The use of alcohol is widespread in sports and is often used as a form of celebration or relaxation by practitioners of physical exercises who, for the most part, tend to consume larger volumes than non-active individuals, without reflecting on the effects that can be caused by this intake. Based on the relevance of the topic, the aim of this study was to clarify the effects of alcohol consumption on the hypertrophy process. The present study was carried out through a literature review, the information was obtained from scientific books; of journals and scientific research sites on the internet, considering the English, Portuguese and Spanish languages ​​for research, with the search terms registered in the Health Sciences Descriptors (DeCS). Focusing on analyzing the interaction with mechanisms involved in protein signaling and other key variables for muscle hypertrophy, as well as the impacts generated by consumption and the risks involved in sports performance. In general, acute alcohol consumption, often consumed by athletes, potentially affects protein synthesis, sleep quality, hormonal and immune function, hydration status, production of reactive oxygen species (ROS), so that the risk of muscle injuries can be increased, as well as the recovery process. Consumption should be discouraged and more studies are needed, mainly with the administration of moderate to low doses, for a better understanding of the generated effects.